Preparation and Properties of Polymer/Vermiculite Hybrid Superabsorbent Reinforced by Fiber for Enhanced Oil Recovery - Fayang Jin; Rui Liu; Wanfen Pu; Cailin Wen (Journal of Chemistry)
A series of polymer/clay hybrid superabsorbent composites (SACFs) comprising acrylamide, acrylic acid, sodium 2-acrylamido-tetradecyl sulfonate, fiber, and vermiculite by in situ intercalation and exfoliated method was successfully synthesized. The structure of SACFs was characterized by IR, SXRD, and SEM measurements. Much notable absorbency for SACF-2 was observed compared to that for SACF-1 in the absence of hydrophobic group in the high cationic solution due to the alkyl carbon chain and sulfonic acid group of hydrophobic moistures protecting the cations from attacking the carboxylate groups. What is more, high temperature fiber which acts as bridge connection for the polymeric network structure enhanced both toughness and strength for SACF-4 in the harsh conditions. At the total dissolved substance of 212000 mg/L for Tarim Basin injected water and the temperature of 120°C, desired absorbency as well as water retaining property for SACF-4 was observed during the long period of thermal ageing. Core flooding experiments demonstrated that SACFs could migrate as amoeba in the porous medium and accumulated in the narrow channel to adjust injection profile, promoting the subsequent water diverting into the unswept zones. Finally, characteristic parameters for SACFs calculated from flooding experiment further confirmed these polymer/clay hybrid composites reinforced by fiber would have robust application in the mature oilfield for profile control.